Enhancement Financial Literacy of Rural Communities Through Training and Mentoring: Case Study in South Toapaya Village, Toapaya Bintan, Riau Islands - Hartoto; Atep Jejen; Rosada Yulianti Naulina; Ida I Dewa A Yayati Wilyadewi; Putu Herny Susanti; Abdul Rosid (PT Inovasi Pratama Internasional, 2023)
The discussion in this service discusses the importance of financial literacy, especially in rural communities, and focuses on training and development approaches as a solution to increase it. The core of the discussion is as follows: 1) The Importance of Financial Literacy: Financial literacy is an individual's ability to understand and manage personal finances. It is very important, especially in rural communities, to avoid excessive debt and make wise financial decisions; 2) Training and Mentoring Methods: This article highlights training and mentoring methods as effective solutions in increasing financial literacy. This approach helps individuals understand financial concepts, manage budgets, and make smart financial decisions; 3) Financial Assistance: Financial assistance is an important component in developing financial literacy. It provides personalized guidance in managing personal finances, understanding financial products and services, and planning for the financial future; 4) Continuous: It is important to maintain ongoing assistance to support increased financial literacy. This includes regular training, individual counseling, and ongoing access to financial resources and information; 5) Case Study in South Toapaya Village: This article also introduces a case study in South Toapaya Village, which shows how a training and development approach was used to increase financial literacy in a rural community that faced obstacles in terms of accessibility to financial services; 6) Expectations and Contributions: It is hoped that the results of this study will provide valuable insight into efforts to increase financial literacy in rural areas and contribute to improved policies and practices in developing financial literacy in rural communities; and This research provides an in-depth understanding of efforts to increase financial literacy in rural communities through training and development approaches. It is hoped that the results of this research will help rural communities around the world to manage their finances better and achieve greater financial well-being.